Purification and Characterization of the Soluble Methane Monooxygenase of the Type II Methanotrophic Bacterium Methylocystis sp. Strain WI 14 - Grosse, Stephan (American Society for Microbiology, 1999)
Methane monooxygenase (MMO) catalyzes the oxidation of methane to methanol as the first step of methane degradation. A soluble NAD(P)H-dependent methane monooxygenase (sMMO) from the type II methanotrophic bacterium WI 14 was purified to homogeneity. Sequencing of the 16S rDNA and comparison with that of other known methanotrophic bacteria confirmed that strain WI 14 is very close to the genus Methylocystis. The sMMO is expressed only during growth under copper limitation (<0.1 μM) and with ammonium or nitrate ions as the nitrogen source. The enzyme exhibits a low substrate specificity and is able to oxidize several alkanes and alkenes, cyclic hydrocarbons, aromatics, and halogenic aromatics. It has three components, hydroxylase, reductase and protein B, which is involved in enzyme regulation and increases sMMO activity about 10-fold. The relative molecular masses of the native components were estimated to be 229, 41, and 18 kDa, respectively. The hydroxylase contains three subunits with relative molecular masses of 57, 43, and 23 kDa, which are present in stoichiometric amounts, suggesting that the native protein has an α(2)β(2)γ(2) structure. We detected 3.6 mol of iron per mol of hydroxylase by atomic absorption spectrometry. sMMO is strongly inhibited by Hg(2+) ions (with a total loss of enzyme activity at 0.01 mM Hg(2+)) and Cu(2+), Zn(2+), and Ni(2+) ions (95, 80, and 40% loss of activity at 1 mM ions). The complete sMMO gene sequence has been determined. sMMO genes from strain WI 14 are clustered on the chromosome and show a high degree of homology (at both the nucleotide and amino acid levels) to the corresponding genes from Methylosinus trichosporium OB3b, Methylocystis sp. strain M, and Methylococcus capsulatus (Bath).